MENINGKATKAN DISIPLIN DAN KARAKTER TARUNA MELALUI PEMBINAAN PENDIDIKAN KETARUNAAN YANG HUMANIS DI SEKOLAH KEDINASAN BADAN PENGEMBANGAN SUMBER DAYA MANUSIA PERHUBUNGAN - Sukarwoto, Sukarwoto; Wimatra, Ayub; Caesar Akbar, Muhammad; Tegar Amalillah, Caesario (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
One way to improve discipline and foster good cadet character is to do it on the basis of evaluation and mapping out what factors support achieving this. Many aspects affect a person's level of achievement and discipline, 3 of which are learning motivation, family factors and the educational environment. The purpose of this study was to determine the effect of learning motivation, parental motivation and the educational environment in official schools on the academic achievement of Medan Aviation Polytechnic Cadets as well as to describe the social competence of educators and caregivers in building the excellence of cadets at the Medan Aviation Polytechnic. This research is qualitative research, case study design. Data collection techniques using interviews, observation, and documentation. The data obtained were analyzed using a qualitative descriptive analysis technique which was carried out comparatively. The results of the study prove that the adoption of parenting patterns of one another has a significant effect on creating an atmosphere of achievement and is able to turn the Medan Polytechnic into a cheerful campus without losing moral and ethical values and respecting each other both internally and externally.